High efficiency focusing vortex generation and multichannel multiplexing based on terahertz metasurfaces - Wenyu Li; Tianhua Meng; Lijuan Dong; Lixiang Liu; Jingyu Liu; Guozhong Zhao (Scientific Reports)
Abstract Single-function metasurfaces can only perform one task and thus cannot satisfy the demands of many advanced applications. Employing multifunctional and multiplexing metasurfaces considerably increases the integration density of functional devices. Therefore, orbital angular momentum (OAM) multiplexing metasurfaces have been designed to increase transmission capacity. In this study, a bilayer Pancharatnam–Berry phase unit cell operating at two frequencies in the terahertz (THz) band is proposed. The unit cell has a sub-wavelength thickness that can be used as a functional element for constructing ultrathin and compact metasurfaces for wavefront manipulation. Cross-polarization conversion ratio of 86.3% and 88.5% are obtained at the two frequencies, respectively. We design three multifunction metasurfaces to verify the method. First, two vortex metalenses are designed to focus vortex beams in the sub-wavelength scale at various frequencies. Furthermore, multichannel OAMs with various modes and arbitrary shape of OAM beam arrays can be realized using segmented metasurfaces. Finally, multichannel OAM multiplexing with the frequency selection and polarization dependence were simultaneously realized on a metasurface. Such metasurfaces can be used to realize large-capacity and high-spectrum-efficiency OAM communication. This paper contributes to the disciplines of photonic integration, multiplexing, and multifunctional metasurfaces.